"Life-changing things happen": The role of residential education in the transformation of adults' learning and lives. Issue 6 (23rd May 2018) - Clancy, Sharon Louise; Holford, John
Abstract : Purpose: The purpose of this paper is to examine the implications for adults of learning in a residential context and whether the residential aspect intensifies the learning process, and can lead to enhanced personal transformation, moving beyond professional skills and training for employability. Design/methodology/approach: The paper reports on research, conducted in 2017, with 41 current and former staff and students (on both short courses and longer access courses) in four residential colleges for adults: Ruskin, Northern, Fircroft and Hillcroft Colleges. Findings: Key findings include the powerful role residential education plays in accelerating and deepening learning experiences, particularly for adults who have faced extraordinary personal and societal challenges and are second chance learners. The colleges, all in historic settings, confer feelings of worth, security and sanctuary and the staff support – pastoral and academic, bespoke facilities and private rooms are vital enabling mechanisms. Seminar-style learning creates opportunity for experiential group learning, helping to foster critical thinking and challenge to mainstream views. Social implications: The colleges' ethos, curricula and traditions foster among students an "ethic of service" and a desire to offer "emotional labour" to their own communities, through working for instance in health and social care or the voluntary sector. Originality/value: Little research has been undertaken in contemporary settings on the impact of learning in a residential environment, particularly for second chance learners and vulnerable adults. Still less research has examined the wider implications of learning in a historic building setting and of learning which extends into critical thinking, intellectual growth, transformation and change.